Understanding the ecology of medium-sized carnivores (Mammalia: Carnivora) from a Tropical Dry Forest in Colombian Caribbean - Gómez-Ruiz, Daisy A.; Sánchez-Giraldo, Camilo; Parra, Juan L.; Solari, Sergio (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
Fauna in Tropical Dry Forest (TDF) is highly dependent on water availability due to a marked seasonality in precipitation. There are few studies addressing carnivore’s ecology and the role of seasonality of TDF in Neotropics. We used scent-station and camera trapping to assess seasonal changes in occurrence and habitat use probability with seasonality. We also described activity patterns and collected fresh scats to describe diet for small sized carnivore species in a TDF fragment in the Colombian Caribbean region. We present information regarding: Cerdocyon thous, Leopardus pardalis, and Procyon spp. The analysis showed a significantly higher occurrence probability during the dry season for the three species, and no differences in the detection probability between seasons. The diet of C. thous included 24 different food items; for L. pardalis it was composed of seven items, and finally, 25 food items were identified in the diet of Procyon spp. We found that the three species presented activity patterns corresponding with previous studies. Finally, our results reflect that these species are probably making more/larger habitat use during the dry season than in the wet season, because the area has permanent water ponds by which limited resources (such as water and food) are available almost constantly in this natural reserve.
Keywords: Cerdocyon; Diet; Leopardus; Occupancy; Procyon